Let's evaluate every function for the given values:
f(x)= (x+5)(2x+3)(x-7)
x=5
f(5)=(5+5)(2*5+3)(5-2)=(10)(13)(2) ≠ 0
Therefore, this option doesn't work
f(x)=(x+5)(3x+2)(x-7)
x=5
f(5)=(5+5)(3*5+2)(5-2)=(10)(17)(3) ≠ 0
Therefore, this option doesn't work
f (x) = (x – 5) (2x - 3) (x + 7)
x=5
f(5) = (5-5)(2*5-3)(5+7)=(0)(7)(12)=0
x=2/3
f(2/3) = (2/3-5)(2*2/3 - 3)(2/3+7)=(-13/3)(-5/3)(23/3)≠0
Therefore, this option doesn't work
f(x) = (x – 5) (3x – 2) (x + 7)
x=5
f(5) = (5-5)(3*5-3)(5+7)=(0)(7)(12)=0
x=2/3
f(2/3) = (2/3-5)(3*2/3 - 3)(2/3+7)=(-13/3)(0)(23/3)=0